Spaces of entire functions represented by vector valued Dirichlet series of two complex variables - Sharma, Archna; Srivastava, G. S. (Acta et commentationes Universitatis Tartuensis de mathematica, 2015)
Let Y be the space of all entire functions f : ℂ2 → E defined by the vector valued Dirichlet series, where E is a complex Banach algebra with the unit element. We study various topologies defined on the space Y and characterize continuous linear transformations on Y.